Avaliação cienciométrica do adenocarcinoma de próstata, utilizando o fish como ferramenta citomolecular para análise do gene PTEN, na base de dados SCOPUS no período de 2005 a 2015 - Luz, Willame de Araújo (2016)
Cancer is defined as a chronic multifactorial disease, characterized by the uncontrolled growth of cells that invade tissues and organs and can spread to other body regions. It s a major public health problem worldwide, especially in developing countries due to the accelerated growth of the population of higher age group. This scientometric study emphasized in the evaluation of prostate adenocarcinoma using FISH as citomolecular tool for analysis of the PTEN gene in Scopus database in the period 2005-2015. The study survey was conducted using the keywords: "prostatic neoplasms and PTEN and FISH". Different approaches have been made to go throught the analysis of the scientific production of the articles included in this study as the type of publication (experimental or review ), the number of articles - year , authors, scientific areas, journals, impact factor of the journals that published, among others. As a result, it was observed that the number of publications throughout the study period undergoes variation over ten years. Magazines belonging to developed countries show that they invest in cutting-edge research and are dominant as to its scientific prestige. The Brazilian scientific production has grown significantly in recent years. The intellectual, social and economic impact of publications produced in Brazil is still low significance and has much to grow, a fact that should be changed with greater financial investment by government as private institutions in scientific production area, thus improving the credibility of research institutions and our researchers. Therefore, it is concluded that this scientometrical analysis have shown the quantitative studies on prostate carcinoma, highlighting the importance of each of the proposed objectives, seeking alternatives to improve the growth of science and the visibility of productions on this topic in the global scientific activity.